Pengenalan Komponen Pneumatik di SMK Negeri 5 Kota Bekasi pada Masa Pandemi Covid-19 Menggunakan Media Pembelajaran Berbasis Augmented Reality (AR) - Oditya Retno, Citra; Maruddani, Baso; Sukardjo, Moch (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2023)
Pneumatics learning in vocational schools during the pandemic faced challenges due to limited hands-on practice. Augmented Reality (AR) is expected to be an interactive learning media solution that can increase student motivation and understanding. This study used the Research and Development (R&D) method with the ADDIE model through the stages of analysis, design, development, implementation, and evaluation. Validation was carried out by experts in material, media, and instructional design, as well as individual and small group trials on 11th-grade Industrial Electronics Engineering students. The developed AR media received a "very feasible" category from the experts and a positive response from students with an average feasibility score above 80%. The use of AR was also proven to help students visualize the components and workings of pneumatic systems more realistically. These results indicate that AR-based learning media has great potential for widespread implementation in vocational education.